Procesos lectores en alumnos de 4° grado de primaria de instituciones educativas pública y privada de Ventanilla - Gutiérrez Palomino, Edith Laura (2012)
The investigation had as purpose to descriptive and compares the psychological processes of the reading between the students for fourth grade of primary education to students of public and private schools, both located in Pachacutec. The sample consisted of 60 students, 30 students in each school of a socioeconomic low level to which there was applied the Battery of Evaluation of the Reading Processes (PROLEC) elaborated for Cuetos , Rodríguez and Ruano (2000). Adapted by Guevara (2009). We used the Mann-Whitney U statistic and found significant differences in the tasks of letter name and sound, grammatical structure, sentence comprehension and reading comprehension, for students of the private school versus public institution, although both groups are below the required standards as good readers.